Rivalitas Arab Saudi Dan Iran Di Timur Tengah Pada Arab Spring Suriah Tahun 2011-2016 - Mustahyun, Mustahyun (Journal of Islamic World and Politics, 2017)
Conflicts have never been far from Middle East. Arab Saudi and Iran actively involve in the conflict In order to maintain their hegemony and national interest such as in Syria. For instance, in the Arab Spring both countries involved in the proxy war. Saudi supports the opposition movement asking for revolution and resignation of Basar regime while Iran totally supports the Bashar al-Assad. The involvement of both countries in Syria’s conflict shows the strategic position of Syria in order to keep Saudi’s and Iran’s interest and their political power at Middle East. This study aims to explore rivalry of Saudi and Iran at Syria especially in the Arab Spring from 2011 to 2016. There are two main issues to discuss in this study namely how Saudi and Iran participate in the conflict and what is the national interest of both countries encouraging them to participate in the conflict.Timur Tengah tidak pernah lepas dari konflik. Arab Saudi dan Iran seringkali menjadi aktor yang terlibat konflik. Keterlibatan mereka karena kepentingan national, seperti yang terjadi di Suriah. Konflik Suriah berawal dari gejolak Arab Spring dan menjadi arena Proxy War antara kubu Arab Saudi dan kubu Iran. Arab Saudi mendukung perlawanan Oposisi terhadap rezim, sedangkan Iran totalitas mendukung Presiden Bashar al-Assad. Dukungan Arab Saudi dan Iran dalam bentuk finansial dan militer. Kehadiran Arab Saudi dan Iran, menegaskan bahwa Suriah sebagai wilayah yang sangat strategis dalam mencapai pengaruh politik di Timur Tengah. Tulisan ini bertujuan melihat Rivalitas Arab Saudi dan Iran di Suriah pada peristiwa gejolak Arab Spring tahun 2011-2016. Rivalitas kedua negara tersebut dalam rangka mencapai kepentingan nasional.